Courier Assignment and Routing Problem Algorithm in Online Food Delivery System with Multi-Customer Delivery Patterns - Meilanitasari, Prita; Putri, Maulin Masyito; Agustin, Ilda Auly Sita; Ibrahim, Muhammad Faisal; Arumjani, Dwi Sekar (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2025)
Online food delivery (OFD) businesses face several challenges, including the need for fast deliveries, a high volume of orders, and effective route planning to optimize service efficiency. This study employs the Meal Delivery Routing Problem (MDRP) algorithm to address issues related to courier assignment and capacity management in food delivery operations. The research focuses on scenarios involving a single courier, a single merchant, and multiple demand nodes. Two main methods were used in the study: (1) The Maximum Covering Model (MCM) algorithm, which identifies the coverage area of the courier, and (2) The Flexible Meal Delivery Assignment and Routing Problem (FMD-ARP) algorithm, which tackles routing challenges. Various scenarios were tested to validate the model based on the chosen routes. The aim of this research is to develop a new model and algorithm that reduces delivery time and increases the number of orders that couriers can handle. After processing and analyzing the numerical data, the study identified the most effective scenario that led to improved delivery times and benefits for couriers, enabling them to manage more orders and achieve faster delivery compared to existing algorithms.